Analysis of Student Needs for the Use of Electronic Modules in Set Topic - Ade Irma; Al Jupri; Jarnawi Afgani Dahlan; Nanang Priatna (Juring (Journal for Research in Mathematics Learning), 2025)
This study seeks to probe and gain in-depth insight into students' needs and opinions regarding the development of an electronic module for sets. The research method used is a mixed method, combining quantitative and qualitative approaches to obtain comprehensive data. The sampling technique was purposive sampling, with the sample criteria being active regular class students from the class of 2023 who had previously taken sets and logic courses. The research instruments used consisted of a Likert-scale questionnaire and an interview sheet, where the questionnaire results were analysed using descriptive statistics to determine the average level of students' need for an electronic module. Based on the descriptive statistical analysis, the average score obtained was 23.77, which is categorised as needed. These results indicate that the majority of students responded positively and supported the idea of developing this electronic module. These quantitative findings were reinforced by the results of qualitative interviews, which also showed positive student responses regarding the need for an electronic module to support independent learning. The conclusion of this study confirms that the development of an electronic module for sets is highly relevant, and the results can serve as a basis and reference for further research in the future.